Three-stage laparoscopic surgery in a morbidly obese patient with Hinchey III diverticulitis: a case report - Takako Tanaka; Yoshiaki Kita; Shinichiro Mori; Kenji Baba; Kan Tanabe; Masumi Wada; Yusuke Tsuruda; Kiyonori Tanoue; Shigehiro Yanagita; Kosei Maemura; Shoji Natsugoe (Surgical Case Reports, 2019)
Abstract Background Perforated diverticulitis with purulent peritonitis (Hinchey III diverticulitis) has traditionally been treated with a Hartmann’s procedure in order to avoid the considerable postoperative morbidity and mortality associated with one-stage resection and primary anastomosis. Although there have been reports regarding laparoscopic lavage as the initial treatment of perforated Hinchey III diverticulitis, a formal treatment strategy has not been established yet. We performed a three-stage surgery, including laparoscopic lavage and drainage with diverting ileostomy (first stage), laparoscopic sigmoidectomy (second stage), and ileostomy closure (third stage) in a morbidly obese patient with Hinchey III diverticulitis. Case presentation A 31-year-old man who presented with abdominal pain was diagnosed with perforated diverticulitis and sent to our hospital for evaluation. He had morbid obesity (body mass index (BMI) 50 kg/m2), acute renal failure, and uncontrolled diabetes. We performed an emergency operation including laparoscopic lavage and drainage with a diverting ileostomy for this case of Hinchey III diverticulitis. Fifteen months after the first-stage surgery, we performed laparoscopic sigmoidectomy as the second stage. Finally, 5 months later, we performed ileostomy closure. The patient recovered without significant complications. Conclusion Three-stage surgery including early laparoscopic lavage and proximal diversion for morbidly obese, comorbid patients with Hinchey III diverticulitis may be indicated in the acute phase to avoid perioperative complications and permanent colostomy creation.